Analysis of factors that are the challenges of digital transformation in public service complaint management through the SP4N-LAPOR! Application in the Ombudsman of the Republic of Indonesia - Utama, Dana; Indiyati, Dian (Global Academy of Business Studies, 2025)
Purpose: This study aims to analyze the challenging factors in the digital transformation of public service complaint management through the SP4N-LAPOR! Application at the Ombudsman of the Republic of Indonesia. Methodology/approach: The research adopts a quantitative approach, collecting data through interviews and questionnaires from employees/assistant managers of SP4N-LAPOR! at the Ombudsman of the Republic of Indonesia. Exploratory Factor Analysis (EFA) serves as the analytical method to identify the primary factors influencing difficulties and challenges in the digital transformation process. Results/findings: The analysis reveals several challenging factors in the digital transformation of managing public service complaints through the SP4N-LAPOR! Application at the Indonesian Ombudsman. The identified challenge factors, ranging from the most dominant to less prominent, include Digital Capability, Information Network Systems, Complaint Management, Digital Solutions, Leadership 4.0, Business Ecosystem, Integrated Regulation, Digital Talent, Digital Conversion and Digital Implementation. Conclusion: Digital transformation of complaint management at the Ombudsman of Indonesia faces major challenges, notably limited digital capability (34.93%), hindering SP4N-LAPOR! implementation effectiveness and overall public service efficiency. Limitations: This research aimed to identify factors challenging the digital transformation of public service complaint management, providing a foundation for future studies to develop effective strategies for improvement. However, the study’s respondents were limited to employees or assistants of the Ombudsman of the Republic of Indonesia, restricting broader generalization. Contribution: This article contributes to a comprehensive understanding of critical aspects essential for improving the implementation of digital transformation in managing public service complaints.